Rational mutagenesis of cyclodextrin glucanotransferase at the calcium binding regions for enhancement of thermostability - Goh, Poh Hong (MDPI, 2012)
Studies related to the engineering of calcium binding sites of CGTase are limited. The calcium binding regions that are known for thermostability function were subjected to site-directed mutagenesis in this study. The starting gene-protein is a variant of CGTase Bacillus sp. G1, reported earlier and denoted as -parent CGTasenorm of matrix herein. Four CGTase variants (S182G, S182E, N132R and N28R) were constructed. The two variants with a mutation at residue 182, located adjacent to the Ca-I site and the active site cleft, possessed an enhanced thermostability characteristic. The activity half-life of variant S182G at 60 °C was increased to 94 min, while the parent CGTase was only 22 min. This improvement may be attributed to the formation of a shorter α-helix and the alleviation of unfavorable steric strains by glycine at the corresponding region. For the variant S182E, an extra ionic interaction at the A/B domain interface increased the half-life to 31 min, yet it reduced CGTase activity. The introduction of an ionic interaction at the Ca-I site via the mutation N132R disrupted CGTase catalytic activity. Conversely, the variant N28R, which has an additional ionic interaction at the Ca-II site, displayed increased cyclization activity. However, thermostability was not affected.